Special paper“Leaving nothing behind”: is the bioresorbable vascular scaffold a new hope for patients with coronary artery disease? - Lesiak, Maciej; Araszkiewicz, Aleksander (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Despite significant advances in design and technology of drug eluting stents (DES) and improved long-term outcome of patients treated with percutaneous coronary intervention, the implantation of metallic stents is associated with some limitations. Multiple stents, covering long coronary segments substantially affect vasomotion, changing the vessel into a rigid tube. Bioresorbable vascular scaffolds (BVS) promise complete bioresorption after 2 to 3 years, vessel lumen enlargement, reduction of the plaque to media ratio, and restoration of vasomotion. Thus BVS seems to be a new, promising, and perhaps even a breakthrough invasive treatment for patients with coronary artery disease. The results of randomised trials and registries confirm the efficacy and safety of the BVS, provided the compliance with the technical aspects of implantation. A key role plays also the selection of patients who could potentially benefit most from the implantation of the BVS. The idea of “leaving nothing behind” after percutaneous coronary interventions is a very exiting concept in modern interventional cardiology. If current technology meets the challenge, major limitations will be overcome, and scaffolds prove to be at least as safe and effective as current DES, than in a long run we will be facing a real breakthrough not only in cardiology, but generally in medicine.